New insights into the evolutionary conservation of the sole PIKK pseudokinase Tra1/TRRAP. (26th November 2019) - Elías-Villalobos, Alberto; Fort, Philippe; Helmlinger, Dominique
Abstract : Phosphorylation by protein kinases is a fundamental mechanism of signal transduction. Many kinase families contain one or several members that, although evolutionarily conserved, lack the residues required for catalytic activity. Studies combining structural, biochemical, and functional approaches revealed that these pseudokinases have crucial roles in vivo and may even represent attractive targets for pharmacological intervention. Pseudokinases mediate signal transduction by a diversity of mechanisms, including allosteric regulation of their active counterparts, assembly of signaling hubs, or modulation of protein localization. One such pseudokinase, named Tra1 in yeast and transformation/transcription domain-associated protein (TRRAP) in mammals, is the only member lacking all catalytic residues within the phosphatidylinositol 3-kinase related kinase (PIKK) family of kinases. PIKKs are related to the PI3K family of lipid kinases, but function as Serine/Threonine protein kinases and have pivotal roles in diverse processes such as DNA damage sensing and repair, metabolic control of cell growth, nonsense-mediated decay, or transcription initiation. Tra1/TRRAP is the largest subunit of two distinct transcriptional co-activator complexes, SAGA and NuA4/TIP60, which it recruits to promoters upon transcription factor binding. Here, we review our current knowledge on the Tra1/TRRAP pseudokinase, focusing on its role as a scaffold for SAGA and NuA4/TIP60 complex assembly and recruitment to chromatin. We further discuss its evolutionary history within the PIKK family and highlight recent findings that reveal the importance of molecular chaperones in pseudokinase folding, function, and conservation.